2016
DOI: 10.1055/s-0035-1570503
|View full text |Cite
|
Sign up to set email alerts
|

Spare Roof Technique: A Middle Third New Technique

Abstract: To our knowledge, the spare roof technique (SRT) is the first technique that is based on a complete skeletonization/preservation of the upper lateral cartilages. This technique is used to keep the natural roof of the nose's middle third, while dehumping and/or correcting the crooked septum. From January 2014 till March 2015, a total of 40 rhinoplasties were performed through the SRT: 28 reduction rhinoplasties, 6 complex crooked noses (with extracorporeal septoplasty), and 6 mixed cases. The SRT is an excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The dorsal modulation techniques allows one to reshape this S-shaped bone and the underlying cartilaginous midvault convexity defect. 4 Also, we have observed that, in the vast majority of patients, the nasal hump had no ethmoid bone underneath it; therefore, there should be no need to address it. Unnecessary removal of the posterior ethmoidal plate may lead to sinking of the overlying the nasal bones when lowering the nasal dorsum, creating a visible step.…”
Section: Discussionmentioning
confidence: 91%
“…The dorsal modulation techniques allows one to reshape this S-shaped bone and the underlying cartilaginous midvault convexity defect. 4 Also, we have observed that, in the vast majority of patients, the nasal hump had no ethmoid bone underneath it; therefore, there should be no need to address it. Unnecessary removal of the posterior ethmoidal plate may lead to sinking of the overlying the nasal bones when lowering the nasal dorsum, creating a visible step.…”
Section: Discussionmentioning
confidence: 91%
“…No PPE excision was noted. Additionally, in a cadaveric study, an intact cartilage vault was found after bony cap removal 9 …”
Section: Discussionmentioning
confidence: 95%
“…Additionally, in a cadaveric study, an intact cartilage vault was found after bony cap removal. 9 To investigate the relationship between the PPE and the starting point of the nasal hump, the BC distance was assessed. In our study, the BC distance measured 0 mm in 39 of 100 patients (39%), meaning that there was no cartilaginous septum below the starting point of the nasal hump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…he spare roof technique is a middle-third preservation technique, described in 2016 by Ferreira et al, that allows the surgeon to isolate the entire cartilaginous roof of the middle third without splitting the upper lateral cartilages among them. 1 The spare roof technique includes ostectomy of the bony cap. [1][2][3][4] However, taking into account the clinical and surgical experience acquired over the past years, the authors consider that for patients with V-shaped nasal bones, it would be possible to dehump the nose while preserving the dorsal keystone area.…”
mentioning
confidence: 99%